2022
DOI: 10.3390/su14148789
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cultural Experiences with Loyalty towards Hotel Services: The Mediating Role of Customer Satisfaction

Abstract: The increasing role of the customer experience, based on the feelings the customers acquire from the interaction with a firm’s product and services, has been considered an effective influence on customer satisfaction and loyalty. Customer satisfaction also plays a linking role in the performance–loyalty link. This study, therefore, investigated the effect of the social- and cultural-experience dimensions on loyalty towards hotel services, with customer satisfaction playing a mediating role. Based on a cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
1
0
Order By: Relevance
“…This implies that restaurant guests make their choices mirrored around their associations. This is supported by assertions that guests are likely to express their individual experiences as a reflection of their cultural backgrounds pointed out by (Ogunnaike et al (2022).…”
Section: The Influence Of the Decision-making Process On The Relation...mentioning
confidence: 78%
“…This implies that restaurant guests make their choices mirrored around their associations. This is supported by assertions that guests are likely to express their individual experiences as a reflection of their cultural backgrounds pointed out by (Ogunnaike et al (2022).…”
Section: The Influence Of the Decision-making Process On The Relation...mentioning
confidence: 78%
“…Marketing strategies are plans and actions that a marketer uses to achieve specific marketing goals and objectives. Several studies found that the market orientation, innovation orientation, and entrepreneurial orientation have positive effects on the organizational performance, mediated by a competitive advantage and customer value [39]. Adopting effective marketing mix strategies in healthcare services (using the 7 Ps) could also enhance patient satisfaction and loyalty [19].…”
Section: Healthcare Marketing and Customer Attitudesmentioning
confidence: 99%
“…Customer satisfaction has long been viewed as a key determinant of loyalty intentions [16,59,60]. In other words, satisfied customers tend to hold more favorable attitudes toward current providers, making them more likely to maintain their existing relationships [61].…”
Section: The Dynamics Of the Satisfaction-loyalty Intentions Linkmentioning
confidence: 99%